Rule growth and government effectiveness: why it takes the capacity to learn and coordinate to constrain rule growth - Adam, Christian; Fernandez-i-Marin, Xavier; Knill, Christoph (2017)
This paper asks whether strong bureaucracies can effectively constrain the continuously growing stock of rules in modern democracies through organizational coordination and learning. To answer this question, the paper analyzes the growth of rule stocks in the areas of environmental policy and social policy in 23 OECD countries over the period between 1976 and 2005. To do so, it develops a new measure of rule growth based on the content of laws and regulations rather than their length. The analysis highlights that effective bureaucracies are indeed better able to contain rule growth in these areas than weak bureaucracies. Since rules have to be implemented, countries suffering from bureaucratic capacity and quality constraints thus appear to be stuck in an implementation deficit trap. Appropriate implementation is not only inherently more challenging for countries with weak public administrations, but the body of rules to be implemented also tends to grow quicker in these countries. - Reproduced.
Keywords: Social policy; environmental policy; Bureaucracy